Bery Engebretsen letter to James J. Dinsmore regarding summer bird sightings, August 20, 1987 - Engebretsen, Beryet al (1987)
Letter from Bery Engebretsen to James J. Dinsmore regarding summer bird sightings, August 20, 1987. This item was submitted past the deadline for the Iowa Ornithologists' Union Quarterly field report of summer 1987. Epson - sheet feed